2020
DOI: 10.4103/psychiatry.indianjpsychiatry_842_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anxiety and depression symptoms in the Albanian general population during the outbreak of COVID-19 pandemic

Abstract: Background: During the COVID-19 pandemic, the Albanian authorities declared mandatory stay-at-home measures, closing businesses, schools, and public places. This study aims to investigate the impact of these immediate changes on the mental well-being of the population. Methodology: Respondents ( N = 1678) aged 18–60 years were selected through a convenient sampling method. A questionnaire was administered online for 26 days, where respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…First of all, the reported level of anxiety and depression were similar to those observed in other studies (see, e.g., Asmundson et al, 2020). Furthermore, we found similar results concerning age as other COVID-19 studies, which showed that younger individuals were more affected by the pandemic than older individuals (Elezi et al, 2020;Huang & Zhao, 2020;Moghanibashi-Mansourieh, 2020;Picaza Gorrochategi et al, 2020;Saravanan et al, 2020;Smith et al, 2020). An interesting finding of our study regards the fact that, whereas anxiety levels were retrospectively reported to have increased in men from before to during the pandemic, this is not the case for women, who did not report a perceived significant increase in their anxiety level.…”
Section: Discussionsupporting
confidence: 90%
“…First of all, the reported level of anxiety and depression were similar to those observed in other studies (see, e.g., Asmundson et al, 2020). Furthermore, we found similar results concerning age as other COVID-19 studies, which showed that younger individuals were more affected by the pandemic than older individuals (Elezi et al, 2020;Huang & Zhao, 2020;Moghanibashi-Mansourieh, 2020;Picaza Gorrochategi et al, 2020;Saravanan et al, 2020;Smith et al, 2020). An interesting finding of our study regards the fact that, whereas anxiety levels were retrospectively reported to have increased in men from before to during the pandemic, this is not the case for women, who did not report a perceived significant increase in their anxiety level.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, our study found indirect pathways to mental health, where younger participants reported prior mental health problems and older participants reported prior physical health problems. In the current study, younger participants also had more indirect stressors associated with the pandemic 16 and reported more COVID-19 experiences. Females and whites reported more anxiety, although this association did not hold in the structural model.…”
Section: Discussionmentioning
confidence: 47%
“…Early studies from the COVID-19 pandemic identify similar concerns to past pandemics regarding mental health 5 , 13 15 . Age appears to be a predictor of mental health problems—younger adults have more difficulty 16 19 . However, another study found that persons older than 85 years had worsened mental health, suggesting a potential U-shape distribution 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 76 studies: 92.1% (n = 70) were cross-sectional studies [13,14,22,26,[28][29][30]34,41,42,46,47,[53][54][55]57,62,65,[69][70][71]75,76,[79][80][81]83], followed by Latin America (6.5%; n = 5) [31,50,58,60,82], Africa (3.9%; n = 3) [36,44,84], Oceania (1.3%; n = 1) [38], and North America (1.3%; n = 1) [78], while two studies included samples from two or more continents [48,56]. None of the studies included in this review were conducted with face-to-face interviews.…”
Section: Resultsmentioning
confidence: 99%